Pengembangan Instrumen Penilaian Higher Order Thinking Skills (HOTS) Pada Mata Pelajaran Korespondensi Kelas X OTP Di Smk Negeri 1 Jombang - Siti Aisah; Triesnina Pahlevi (Universitas Negeri Surabaya, 2020)
The purpose of this study was determine the process of developing Higher Order Thinking Skills (HOTS) assessment instruments in OTP Class X Correspondence Subjects at SMK Negeri 1 Jombang, the quality of Higher Order Thinking Skills (HOTS) assessment instruments, and high-level thinking skills of students. Using R&D methods. The research model was adapted based on Sugiyono's development model which consisted of 7 steps. The study was conducted on 69 students of class X OTP 1 and 2 of SMK Negeri 1 Jombang. The questions consist of 36 multiple choice questions with 5 alternative answer choices. Based on the results of the validation of three experts validator matei, evaluation, and language declared eligible to be tested. based on data analysis, the validity of the questions compared to r table 0.236 there are 25 valid questions and 11 invalid questions, the reliability value of the difficulty of the questions is 0.667 with the category of